Non-Beta-Lactamase-Producing Penicillin-Resistant Enterococcus faecium in a Clinical Setting - Daniel Eymard; Andre Dascal; John Hiscott; Sonia Gioseffini; Janet Stevenson; Joseph Portnoy; Jack Mendelson (Canadian Journal of Infectious Diseases)
Six clinical isolates of Enterococcus faecium highly resistant to penicillin are reported. These strains did not produce beta-lactamase and no plasmid DNA could be detected. It is postulated that the mechanism of resistance is one or more chromosomally mediated alterations of penicillin-binding proteins.